Imperial Benevolence Making British Authority in the Pacific Islands - Samson, Jane (University of Hawaii Press, 1998)
This insightful analysis of British imperialism in the south Pacific explores the impulses behind British calls for the protection and "improvement" of islanders. From kingmaking projects in Hawaii, Tonga, and Fiji to the "antislavery" campaign against the labor trade in the Western pacific, the author examines the deeply subjective, cultural roots permeating Britons' attitudes toward Pacific Islanders. By teasing out the connections between those attitudes and the British humanitarian and antislavery movements, Imperial Benevolence reminds us that nineteenth-century Britain was engaged in a global campaign for "Christianization and Civilization."